Day of the dead - Williams, Kitty, 1958- (Gibbs Smith, 2011)
From the publisher. The Day of the Dead Celebration is the most important holiday of the year in Mexico and parts of the American Southwest, a joyful time when families remember their dead. Day of the Dead provides a colorful look at the iconic folk art and family traditions that play a vital role in the event, which happens across the country from October 31 through November 2.